Body-focused repetitive behaviors and non-suicidal self-injury: A comparison of clinical characteristics and symptom features. (May 2020) - Mathew, Abel S.; Davine, Taylor P.; Snorrason, Ivar; Houghton, David C.; Woods, Douglas W.; Lee, Han-Joo
Abstract: Body-focused repetitive behaviors (BFRBs) and non-suicidal self-injury (NSSI) are recognized as distinct categories in the DSM-5. However, definitions and assessment of NSSI sometimes encompasses behaviors similar to BFRBs, and little data exist about their clinical differences. The current study examined clinical characteristics and symptom features associated with NSSI vs. BFRBs. The current sample included 1523 individuals who endorsed moderate to severe NSSI ( n = 165) or BFRBs: hair pulling group ( n = 102), skin picking group ( n = 216), nail picking group ( n = 253), nail biting group ( n = 487), and cheek biting group ( n = 300). Responders were asked to complete questionnaires on clinical features relevant for BFRBs and NSSI. NSSI and BFRBs had significant differences on several clinical features. Individuals in the NSSI group were more likely than individuals with BFRBs to report engaging in the behavior for social-affective reasons (i.e., to get out of doing something, or receive attention from others). Individuals in the NSSI group were also more likely to engage in the behavior to regulate tension and feelings of emptiness, and to experience relief during the act. In contrast, individuals in the BFRB groups were more likely to engage in the behavior automatically without reflective awareness, to reduce boredom, or to fix appearance. The NSSI group obtained significantly higher scores on questionnaires assessing stress, anxiety, depression, and harm avoidance. Overall, the results showed several notable differences between NSSI and BFRBs that are consistent with clinical literature and definitions of these problems in the DSM-5. Highlights: There are debates on classification of BFRBs and non-suicidal self-injury (NSSI). There is a paucity of research that directly compared BFRBs and NSSI. We examined clinical features of BFRBs and NSSI from a large sample (N = 1523). NSSI is performed less automatically with greater awareness than BFRBs. NSSI is performed more for gratifying social-affective needs than BFRBs.